Analysis of Coastline Changes and the Socio-economic Driving Mechanisms in Shenzhen, China. Issue 6 (2nd November 2017) - Liu, Chaoxian; Wu, Xueling; Cao, Xuelian; Wu, Guofeng
ABSTRACT: In recent decades, human activities have significantly affected coastline changes with the dramatic expansion of coastal cities. In this study the modified normalized difference water index was applied to multi-temporal images of Shenzhen to determine coastlines, and a point-based approach was used to reflect spatial location changes from 1988 to 2015. The results of the stepwise discriminant analytical method and the grey correlation analysis model suggest that socio-economic factors have greatly affected changes in the coastline stability and types. It can be concluded that the population growth factor is responsible for coastline changes, in addition to some economic factors.